Measures of insulin resistance as a screening tool for dysglycaemia in patients with coronary artery disease. A report from the EUROASPIRE V population. (3rd October 2022) - Ferrannini, G; De Bacquer, D; Erlund, I; Gyberg, V; Kotseva, K; Mellbin, L; Norhammar, A; Schnell, O; Tuomilehto, J; Vihervaara, T; Wood, D; Ryden, L
Abstract: Background: The optimal screening strategy for dysglycaemia, including type 2 diabetes (T2DM) and impaired glucose tolerance (IGT), in patients with coronary artery disease (CAD) is debated. Purpose: We tested the hypothesis that measures of insulin resistance by homeostasis model assessment (HOMA) indexes may constitute accurate screening methods in a CAD population. Methods: Insulin, C-peptide, glycated haemoglobin A1c (HbA1c) and an oral glucose tolerance test (OGTT) were centrally assessed in 3534 CAD patients without known dysglycaemia from the EUROASPIRE V survey. Three different HOMA indexes were calculated: HOMA-IR, HOMA2 based on insulin (HOMA2-ins), and HOMA2 based on C-peptide (HOMA2-Cpep). Dysglycaemia was diagnosed based on the two-hour postload glucose (2hPG) value obtained from the OGTT. Information on study participants was obtained by standardised visits. The optimal thresholds of the three HOMA indexes for dysglycaemia diagnosis were obtained by the maximum value of Youden's J statistic on receiver operator characteristics curves. The diagnostic performance of such thresholds was tested for both T2DM (i.e. in reference to a 2hPG value ≥11 mmol/L) and dysglycaemia (i.e. in reference to 2hPG value ≥7.8 mmol/L) and their correlation with several clinical parameters was assessed by Spearman's coefficients. Results: The mean age of the patients was 63 years and 25% were women. Fifty-four percent of the patients had central obesity, 18% were current smokers, mean blood pressure was 133/80 mmHg and mean LDL-cholesterol 2.4 mmol/L. The OGTT revealed that 41% were dysglycaemic (IGT = 24% and T2DM = 16%). Mean insulin, C-peptide and HOMA indexes were significantly higher in patients with vs. without newly detected dysglycaemia (all p<0.0001). Sensitivity and specificity of the three HOMA indexes for the diagnosis of dysglycaemia were low and the associations between 2hPG and the other parameters in the total sample were weak, with Spearman correlation coefficients of 0.15 for fasting insulin, 0.19 for C-peptide, 0.24 for HOMA-IR, 0.18 for HOMA2-ins and 0.22 for HOMA2-Cpep. HOMA-IR, HOMA2-ins and C-peptide were strongly correlated with body mass index and waist circumference (Spearman correlation coefficients ranging 0.43–0.47). Conclusion: Screening for dysglycaemia in CAD patients by insulin, C-peptide, HOMA-IR, HOMA2-ins and HOMA2-Cpep had insufficient diagnostic performance to detect dysglycaemia with reference to the yield of an OGTT, which should still be prioritized. Further studies are warranted to assess whether measures of insulin resistance might be better markers of unfavourable metabolic derangement beyond dysglycaemia. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): European Society of CardiologyErling-Perssons Stiftelse